Thyroglossal Duct Carcinoma Originating in the Hyoid Bone. (1st July 2019) - Kunitomo, Naoki; Fujii, Hiroyuki; Fujita, Akifumi; Hamano, Yumiko; Takanosawa, Minako; Sugimoto, Hideharu
Abstract : Thyroglossal duct (TGD) carcinoma is a rare malignant tumor arising from remnants of thyroid tissue or the wall of the duct and generally occurs along the anatomic course of the TGD. TGD carcinoma originating in the hyoid bone is extremely rare but can occur since the TGD penetrates the hyoid bone on rare occasions. This report describes the case of a 30-year-old man with TGD carcinoma originating in the hyoid bone. Computed tomography demonstrated a mass in the hyoid bone that expanded the cortical bone of the hyoid. The mass had a central solid component with calcification and a marginal cystic component. When we encounter a calcified mass in the hyoid bone, we should consider TGD carcinoma among the differential diagnoses.